Systematic Development of National Guidelines for Obesity Care: the Swedish Approach - Paulina Nowicka; Lovisa Sjögren; Ann-Sofie Bertilsson; Kajsa Järvholm; Fanny Sellberg; Magnus Sundbom; Liv Thalén; Ylva Trolle Lagerros (Obesity Facts, 2024)
Introduction: With the rapid development of treatment modalities for obesity management, there is a growing need for guidelines. This was acknowledged by the Swedish National Board of Health and Welfare and in 2020 the process of producing the first national guidelines for obesity care, including both children and adults, was initiated. The main aim was to ensure equal high standard care throughout Sweden by supporting decision makers to allocate resources to the best knowledge-based care. Methods: The standardized procedures of the National Board of Health and Welfare were applied to construct guidelines in a systematic and transparent way, including priority setting of recommendations and quality indicators to evaluate the progress of implementation. The process involved independent expert committees including professionals and patient representatives, and the guidelines were reviewed through an open public consultation. Results: In total, 20 recommendations were issued encompassing a broad scope, from identification and diagnosis to multiple treatment modalities, embedded in a life course perspective from pregnancy to the elderly, as well as highlighting the need for improved knowledge and competence of health care providers. Conclusions: National guidelines for improved standard care and evidence based and efficient use of health care resources for obesity treatment can be developed in a systematic way with professionals and patient representatives.